The role of selenium in severe fever with thrombocytopenia syndrome: an integrative analysis of surveillance data and clinical data. (September 2022) - Che, Tian-Le; Li, Xin-Lou; Tian, Jian-Bo; Wang, Gang; Peng, Xue-Fang; Zhang, Hai-Yang; Chen, Jia-Hao; Zhu, Ying; Zhang, Wen-Hui; Wang, Tao; Liu, Bao-Cheng; Xu, Qiang; et al.
Highlights: There is a higher incidence of severe fever with thrombocytopenia syndrome (SFTS) in selenium-deficient areas. Mortality of SFTS is higher in severe selenium-deficient areas. Insufficient serum selenium in humans is associated with poor prognosis in SFTS. Abstract: Objectives: Selenium deficiency can be associated with increased susceptibility to some viral infections and even more severe diseases. In this study, we aimed to examine whether this association applies to severe fever with thrombocytopenia syndrome (SFTS). Method: An observational study was conducted based on the data of 13, 305 human SFTS cases reported in mainland China from 2010 to 2020. The associations among incidence, case fatality rate of SFTS, and crop selenium concentration at the county level were explored. The selenium level in a cohort of patients with SFTS was tested, and its relationship with clinical outcomes was evaluated. Results: The association between selenium-deficient crops and the incidence rate of SFTS was confirmed by multivariate Poisson analysis, with an estimated incidence rate ratio (IRR, 95% confidence interval [CI]) of 4.549 (4.215−4.916) for moderate selenium-deficient counties and 16.002 (14.706−17.431) for severe selenium-deficient counties. In addition, a higher mortality rate was also observed in severe selenium-deficient counties with an IRR of 1.409 (95% CI: 1.061−1.909). A clinical study on 120 patients with SFTS showed an association between serum selenium deficiency and severe SFTS (odds ratio, OR: 2.94; 95% CI: 1.00–8.67) or fatal SFTS (OR: 7.55; 95% CI: 1.14–50.16). Conclusion: Selenium deficiency is associated with increased susceptibility to SFTS and poor clinical outcomes. Graphical abstract: This is special type of abstract that is so short and could be inserted after main abstract of article, as a blurb or inserted as annotations into a Table of contents Image, graphical abstract